Daily activities and suspected dementia among community-dwelling older adults: a cross-sectional study - Shuhan Yan; Zihan Geng; Jie Zhang; Huahua Liu; Zhifang Chen; Yaqin Shi; Feng Zhang (BMC Geriatrics)
Abstract Background Dementia is undiagnosed among many older adults, and more than half the people in local communities live with symptoms of dementia are not properly treated. Objective The study aims to explore the relationship between decline of daily activities and the incidence of suspected dementia. Methods A two-stage sampling method was used to conduct a multicenter cross-sectional survey. Older adults who have not been diagnosed as dementia were recruited from the local community. The Revised Hasegawa Dementia Scale (HDS-R) was used to evaluate the cognitive function. We evaluated daily activities from several aspects (bathing, dressing, toileting, grooming, feeding, transportation, walking, telephone, housekeeping, and taking medications). Logistic regression was adopted to assess the influence of daily activities on the risk of suspected dementia after controlling for the covariates. Results The analysis included 2458 individuals. Daily activities included toileting (OR = 1.830, 95%CI 1.581 ~ 2.119), grooming (OR = 1.938, 95%CI 1.659 ~ 2.265), dressing (OR = 1.771, 95%CI 1.542 ~ 2.033), bathing (OR = 1.793, 95%CI 1.591 ~ 2.022), feeding (OR = 1.821, 95%CI 1.565 ~ 2.118), transportation (OR = 1.996, 95%CI 1.743 ~ 2.285), walking (OR = 2.069, 95%CI 1.685 ~ 2.542), telephone (OR = 3.640, 95%CI 2.738 ~ 4.838), housekeeping (OR = 1.415, 95%CI 1.213 ~ 1.649), and taking medications (OR = 1.633, 95%CI 1.451 ~ 1.839) were still related to the incidence of suspected dementia after controlling for age, education, post-retirement work, social activity, drinking, smoking, living with spouses, and diabetes. Conclusions Daily activities were related to the incidence of suspected dementia. Daily activities were affected even if the older adults were not diagnosed as dementia. Timely and accurate diagnosis of dementia should be encouraged among community-dwelling older adults.